2012
DOI: 10.1080/00107514.2011.640146
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic quantum information and time machines

Abstract: Relativistic quantum information combines the informational approach to understanding and using quantum mechanics systems -quantum information -with the relativistic view of the universe. In this introductory review we examine key results to emerge from this new field of research in physics and discuss future directions. A particularly active area recently has been the question of what happens when quantum systems interact with general relativistic closed timelike curves -effectively time machines. We discuss … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 108 publications
1
35
0
Order By: Relevance
“…where the right-hand side shows the equivalent of the conformal time expression in Minkowski time, with + (−) for the future (past) coordinates, we can observe that a physical detector that follows the conformal time of equation (2) (with 0 ϵ = ) corresponds to a detector with time dependent energy-level spacings ( H at o ± ). This observation was confirmed in [7] and [8] via the explicit calculation of the excitation rates and correlation properties of Unruh-DeWitt detectors, coupled to the Minkowski vacuum and given time dependent resonant frequencies according to equation (3). This demonstrated that inertial, energy scaled detectors of this type could indeed couple to the Rindler modes as expected and hence observe the intrinsic entanglement in the quantum vacuum.…”
Section: Rindler and Light Cone Coordinatessupporting
confidence: 61%
See 2 more Smart Citations
“…where the right-hand side shows the equivalent of the conformal time expression in Minkowski time, with + (−) for the future (past) coordinates, we can observe that a physical detector that follows the conformal time of equation (2) (with 0 ϵ = ) corresponds to a detector with time dependent energy-level spacings ( H at o ± ). This observation was confirmed in [7] and [8] via the explicit calculation of the excitation rates and correlation properties of Unruh-DeWitt detectors, coupled to the Minkowski vacuum and given time dependent resonant frequencies according to equation (3). This demonstrated that inertial, energy scaled detectors of this type could indeed couple to the Rindler modes as expected and hence observe the intrinsic entanglement in the quantum vacuum.…”
Section: Rindler and Light Cone Coordinatessupporting
confidence: 61%
“…We have shown that by employing energy-scaled homodyne detection it is possible for two observers, separated by non-trivial distances, to measure the correlations of entangled space-time vacuum modes with sufficient quality so as to be able to implement a QKD protocol. The energy levels of the detectors must change with lab time according to Hamiltonians obeying equation (3). The local oscillators should also follow this scaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel field of relativistic quantum information aims at understanding how relativity affects quantum information tasks [11,12]. Most of hitherto research has focused on modeling and employing localized systems for quantum information processing [13][14][15], while only recently some attention has been drawn towards understanding the influence of gravity on quantum protocols.…”
Section: Introductionmentioning
confidence: 99%
“…A certain type of quantum gates without definite temporal order (acausal gates) has been modeled based on postselected quantum teleportation [6,7]. These gates are referred to as closed timelike curves via quantum postselection (pCTCs, or also known as BSS-CTCs) and their properties have been recently intensively investigated [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%